MEMBANGUN KEWIRAUSAHAAN DI ERA DIGITAL STUDI KASUS DESA PEDALEMAN KECAMATAN TANARA SERANG BANTEN - Firnia, Dewi (Jurnal Pengabdian Dinamika, 2022)
The digital economy can be said to be a new economy because the use and all processes carried outmust be based on the technology that is developing in the current era, this era which is versatile andeasy does not rule out the possibility of making it easier for the wider community to be able tomarket their trade products. The people of Pedaleman Village, Tanara Serang, Banten, are mostlyfarmers and fishermen. Most of the villagers also have jobs as traders. The work owned by thePedaleman village community, who mostly trade, cannot be included in the category of anentrepreneur because entrepreneurs are not just trading or selling but how one can create goods thathave more value, the surplus value created can result in a much higher price of value. The purposeof holding digital era entrepreneurship activities (Digital Business) is to encourage the PedalemanVillage community to be able to compete widely in the digital era business world. The entrepreneuris an activity that can change resources that originally had low-quality products into high-qualityproducts so that they can compete highly in the market because they have innovations that aregeneratedandinnovationsaresoldtothewidercommunity,andthereiscompetitionfrommerchandise that has been given innovation or innovation. changes in the value of a trade. The eraof the industrial revolution 4.0 is an era of collaboration between digitalization and automation byutilizing information technology. The community's choice to be able to understand and apply socialmedia as a market for selling in the digital 4.0 era is the right choice to market widely the businessesowned by the Indonesian people.